2016
DOI: 10.5498/wjp.v6.i1.128
|View full text |Cite
|
Sign up to set email alerts
|

Poor CD4 count is a predictor of untreated depression in human immunodeficiency virus-positive African-Americans

Abstract: Therefore, CD4+ count could be a clinical marker of untreated depression in HIV+. Also, mental health care may be relevant to primary care of HIV+ patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 47 publications
1
14
0
1
Order By: Relevance
“…In our study, higher levels of depression symptoms were associated with higher viral loads, a finding consistent with other studies (Amanor-Boadu et al, 2016;Herkenham & Kigar, 2016). However, this association was only found in women, the group with a smaller sample size.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, higher levels of depression symptoms were associated with higher viral loads, a finding consistent with other studies (Amanor-Boadu et al, 2016;Herkenham & Kigar, 2016). However, this association was only found in women, the group with a smaller sample size.…”
Section: Discussionsupporting
confidence: 92%
“…Anxiety and especially depression have consistently been associated with poor antiretroviral treatment (ART) adherence (Safren et al, 2016;Smith Fawzi et al, 2016;Tao et al, 2016;Tatum & Houston, 2016), and are linked to poor virological control and lower CD4 T cell counts (Amanor-Boadu et al, 2016;Herkenham & Kigar, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This is contrary with result by Bitew et al, who reported CD4 count < 500 cells/μL as a predictive factor of suicidal thoughts with AOR of 2.5 [41]. Amanor-Boadu et al went further and defined CD4 count as a clinical marker of untreated depression in African-American PLHIV [67]. In progressive HIV disease, low CD4 count was associated with AIDS defining illness and increasing mortality, while untreated depression and poor ART adherence were independently associated with poorer CD4 outcomes [63].…”
Section: Discussionmentioning
confidence: 76%
“…Health behaviors, treatment adherence, and use of support and health services could impact aspects of physical and mental health such as immune function and psychiatric symptoms. Prior work published by the investigators reported poor CD-4 count association with poor ART adherence and MDD, which persists where MDD is untreated 5. Faith beliefs could be assessed to help improve adherence and psychiatric symptom treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Comorbidity of HIV+ and depression reportedly could impact health outcomes with clinical, economic, and/or humanistic consequences. Depression rates are higher among HIV+ individuals than the wider US population; higher among HIV+ women, minorities, and individuals with co-existing substance use 511. Depression has been associated with poorer CD-4 T-cell counts, higher HIV+ viral loads, lower antiretroviral therapy (ART) adherence, poorer prognosis, and higher mortality 12–15.…”
Section: Introductionmentioning
confidence: 99%